The action in vivo of glycine betaine in enhancement of tolerance of Synechococcus sp. strain PCC 7942 to low temperature. - Deshnium, P (1997)
The cyanobacterium Synechococcus sp. strain PCC 7942 was transformed with the codA gene for choline oxidase from Arthrobacter globiformis under the control of a constitutive promoter. This transformation allowed the cyanobacterial cells to accumulate glycine betaine at 60 to 80 mM in the cytoplasm. The transformed cells could grow at 20 degrees C, the temperature at which the growth of control cells was markedly suppressed. Photosynthesis of the transformed cells at 20 degrees C was more tolerant to light than that of the control cells. This was caused by the enhanced ability of the photosynthetic machinery in the transformed cells to recover from low-temperature photoinhibition. In darkness, photosynthesis of the transformed cells was more tolerant to low temperature such as 0 to 10 degrees C than that of the control cells. In parallel with the improvement in the ability of the transformed cells to tolerate low temperature, the lipid phase transition of plasma membranes from the liquid-crystalline state to the gel state shifted toward lower temperatures, although the level of unsaturation of the membrane lipids was unaffected by the transformation. These findings suggest that glycine betaine enhances the tolerance of photosynthesis to low temperature.